Biomass-derived multifunctional 3D film framed by carbonized loofah toward flexible strain sensors and triboelectric nanogenerators. (March 2023) - Tang, Wenyang; Fu, Chiyu; Xia, Liangjun; Su, Lingling; Lyu, Pei; Fu, Zhuan; Gong, Junyao; Li, Li; Zhang, Chunhua; Xu, Weilin
Abstract: The ever-increasing complexity of social activities has yielded the call for wearable electronics with combined high performance and multifunction. Although the introduction of three-dimensional (3D) structures has proved to be a promising approach, the complicated fabrication process, hazardous precursors, and undesirable performance of 3D structures may pose challenges for developing advanced electronics. Herein, a green and cost-effective carbonized loofah (CL) was fabricated into a versatile flexible electronic for both strain sensing and energy harvesting. The maintained 3D architectures of CL have a promotive effect on improving the responding sensitivity. Therefore, the CL-based strain sensor exhibits advanced characteristics, such as ultrahigh sensitivity (GFmax = 14, 639.06), short response time (30 ms), ultralow detection limit (0.01% strain), and good durability (2000 cycles). These features endow the CL with efficient discernibility to monitor multiple complicated human activities (e.g., pulse rate, breathing, phonation). Furthermore, the CL can act as a flexible triboelectric nanogenerator (TENG) for energy collection, providing a potential sustainable energy supply for the continuous working of the sensing system. Therefore, the biomass-derived CL with instinct structures may be a promising platform for the fabrication of multifunctional wearable devices for human health monitoring and portable power sources. Graphical Abstract: ga1 Highlights: A multifunctional wearable electronic was fabricated firstly using carbonized loofah (CL). CL strain sensor performs ultrahigh sensitivity, fast response, and ultralow detection limit. It can precisely detect both tiny and large movements inducted by human activities. Cracks propagation of 3D architectures of CL contributes to its high sensing ability. CL also acts as triboelectric nanogenerator (TENG) for energy harvesting and self-powered strain sensing.